Under What Conditions Can People With Severe Dementia in Nursing Homes Benefit From a Multicomponent Psychosocial Intervention? - Diehl, Kristina; Kratzer, André; Grässel, Elmar (Gesundheitswesen, Supplement, 2023)
Background The majority of psychosocial interventions are considered effective in the treatment of dementia symptoms. However, there are hardly any evaluated concepts for people with severe dementia. An RCT study of patients with severe dementia in nursing homes during the Covid-19 pandemic found no effect of the newly developed multi-component intervention MAKS-s (motor, activities of daily living, cognitive, social version for persons with severe dementia) on patients quality of life, behavioural and psychological symptoms. Material and methods At the end of the controlled phase, 6 months after beginning of the study, the nursing staff of the control groups were also trained in MAKS-s. They were then free to decide whether and how often they wanted to use MAKS-s (open phase). By means of a written follow-up survey, conconducted with trained therapists, after another 6 months, predictors for positive effects of the intervention on people with severe dementia were to be identified. The survey also aimed to identify predictors of therapy fidelity. Data acquisition based on a self-developed questionnaire, assessing the therapists' subjective ratings of the three areas of structure, process and outcome quality of the MAKS-s intervention. Apart from descriptive evaluations, the predictors of benefit for people with severe dementia were analysed using a linear regression model and the predictors of therapy fidelity by using a binary logistic regression model. Results The more pronounced the normative restrictions due to the Covid-19 pandemic were, the more frequently manual deviations were observed. Fewer deviations from the manual were significantly associated with positive effects on people with severe dementia. Conclusion The results indicate the importance of therapy fidelity for the success of MAKS-s intervention. Therapy fidelity is decisive for the extent of the positive effects of MAKS-s, experienced by the therapists. Furthermore, the survey results show that activity-restricting pandemic policies in nursing homes negatively influenced the perceived effectiveness.
CRIS-Team Scopus Importer:2023-10-20
Keywords: Covid-19; dementia; nursing homes; psychosocial intervention; Treatment adherence and compliance